Self-Esteem, Emotional Maturity and Self Efficacy Of Youth Participating in Theathre Performance - Yee, Wendy Mei Tien (2004)
Youth are important assets for the continuous development of the nation. Youth are also in a critical stage for development. Therefore, many youth development programmes have been conducted to help youth to develop and equip them with the necessary attitudes, knowledge and skills to enable them to meet the future challenges and become indispensable leaders of tomorrow. A major developmental task during youth is the creation of a sense of identity. Theatre is one of the most common developmental programme used in the United States, Britain, Canada and Australia because through performing, the youth are able to project a new identity and discover themselves (Courtney, 1980). However, in Malaysia, theatre has not been embarked forcefully as a developmental programme for the youth. Thus, the purpose of this study is to determine whether theatre will be suitable in youth identity development programme in Malaysia. This study determine the effects of theatre performance towards the identity development of the youth; specifically the development of self-esteem, emotional'matbr&y. and-. : , * ' . self-efficacy. Six selected elements of theatre performance were also used to determine their influence towards the development of these three identities. The respondents for this study comprised of all the diploma students majoring in theatre from year one right up to the final year of two higher learning institutions in Malaysia. The number of respondents responded to the self-administered questionnaires were 109. The findings show that majority of the respondents have a high level of self-esteem and self-efficacy. The findings also show that majority of the respondents have a moderate level of emotional maturity but the overall respondents' emotional maturity can be considered high as almost half of the respondents reported to have a high level of emotional maturity. The other findings of this study show that theatre performance had equal influence towards the development of self-esteem, emotional maturity and self-efficacy. Among the six elements of theatre performance, role-playing, improvisation and characterization have the greatest influenced towards the development of the respondents' self-esteem, emotional maturity and self-efficacy. These findings imply that theatre performance is a suitable youth identity development programme as it helps to develop the youths' inner resources, identity, positive attitude and meet the basic needs for youth to be competent. The study recommended that theatre to be incorporated as one of the youth identity development programme in Malaysia, to give greater emphasis and to incorporate the three most influential theatre performance elements; role-playing, improvisation and characterization into other youth development programmes and to incorporate theatre into the academic curriculum in school.